Sexual dysfunctions among patients in a psychiatric hospital (Bangladesh Journal of Psychiatry, 2020)
Information regarding sexual dysfunctions in psychiatric patients is insufficient though it affects a patient’s quality of life in various ways. The objective of this study was to assess the proportion and pattern of sexual dysfunctions among patient’s attending at the National Institute of Mental Health (NIMH), Dhaka. It was a cross-sectional study conducted from 01 February 2015 to 30 June 2015. A total of 161 patients (of 18-50 years of age) selected purposively and were interviewed after getting informed written consent. A semi-structured socio-demographic questionnaire and a pre-tested (Bengali version of) Arizona Sexual Experience Scale (ASEX) were used for collecting data. Sexual dysfunctions were diagnosed by using the Diagnostic and Statistical Manual for Mental Disorders, 5th edition (DSM-5). Results showed that the mean age of the respondents was 35.12(± 8.22) years. Most of them (75%) were aged between 20-40 years. The proportion of sexual dysfunctions was 67% and it was found more among males (70.3%) than females (62.9%). Among males, Erectile Disorder (35.1%) in indoor and Premature Ejaculation (27.3%) in outdoor were more common. Among females, most common sexual dysfunction was Sexual Interest/Arousal Disorder, of which 34.9% was in indoor and 44.4% in outdoor respondents respectively. The proportion of sexual dysfunction was higher in the semi- urban group (75%), those who were educated up to primary level (79%) and belonging to age group 40-50 years (79%). As sexual dysfunction and it’s impact on psychiatric patients are tremendous, sexual functioning of every patient needs special attention, care and early interventions for reducing sufferings.Bang J Psychiatry December 2017; 31(2): 43-47